Edukasi Terhadap Ibu Balita Dalam Upaya Pencegahan Stunting Pada Balita di Posyandu Kelurahan Tungkal - Miskiyah; Daimah, Umi; Rosdiana; Nurayuda; Kamalia, Rita (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Stunting remains a serious public health issue in Indonesia, particularly in areas with low economic status and limited access to healthcare services. Lack of maternal knowledge about balanced nutrition and low participation in Posyandu (integrated health service post) contribute to the high prevalence of stunting. Objective: The purpose of this service was to educate mothers of toddlers about stunting prevention through an interactive counseling program at Posyandu in Kelurahan Tungkal, Muara Enim. Method: This public service was conducted by providing interactive counseling sessions using audiovisual media, distributing educational leaflets, and conducting pre- and post-tests to measure knowledge improvement. The activity involved collaboration between academics, midwives, and local health cadres, targeting 60 participants consisting of pregnant women, mothers of infants, and mothers of toddlers. Result: The results showed a significant increase in participants' knowledge, with the percentage of correct answers rising from 50% (pre-test) to 95% (post-test). The methods used, such as interactive discussions and visual aids, proved effective in enhancing understanding of stunting prevention and balanced nutrition. Conclusion: The program successfully improved mothers' knowledge about stunting prevention and the importance of regular growth monitoring at Posyandu. Sustainable education efforts and community involvement are recommended to further reduce stunting rates.